2002
DOI: 10.1103/physrevlett.89.096102
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Roughening: Fundamental Limits in Si(100) Halogen Etch Processing

Abstract: A dynamical scanning tunneling microscopy and density functional theory study of the thermodynamic stability of halogen-terminated Si(100) surfaces is presented. Significant steric repulsion is shown to exist on all halogen-terminated Si(100) surfaces. This repulsion is the driving force for a roughening phenomenon, which is favored for all halogens except fluorine. Since roughening is an intrinsic property of these surfaces, it sets a lower bound on the atomic scale perfection that can be achieved using halog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 15 publications
3
40
0
Order By: Relevance
“…This fact would imply that etching must stop after 6 min, which seems very unlikely. In addition, features that are commonly attributed to surface etching, like terraces becoming filled with vacancies and pits, or steps becoming rougher with longer exposures, are never observed on any of the surfaces [36][37][38][39][40]. Therefore, we conclude that, in general, etching is not the source of the morphological and structural changes observed on vicinal Si(0 0 1) surfaces.…”
Section: Etchingmentioning
confidence: 64%
“…This fact would imply that etching must stop after 6 min, which seems very unlikely. In addition, features that are commonly attributed to surface etching, like terraces becoming filled with vacancies and pits, or steps becoming rougher with longer exposures, are never observed on any of the surfaces [36][37][38][39][40]. Therefore, we conclude that, in general, etching is not the source of the morphological and structural changes observed on vicinal Si(0 0 1) surfaces.…”
Section: Etchingmentioning
confidence: 64%
“…In particular, at a full monolayer coverage, Br prefers a (3 × 2) reconstruction, that the authors relate to the (3 × 1) reconstruction found experimentally by Chander et al [15]. Very recently, Nakayama et al have proposed a new form of surface modification without the desorption, by recycling the Cl on Si(001) [16], while Hermann et al have shown that halogen terminated Si(001) surfaces are intrinsically unstable and susceptible to spontaneous roughening [17].…”
Section: Introductionmentioning
confidence: 82%
“…We believe, this is due to the fact that it maintains the c(2 × 4) periodicity. Another possibility is that in this geometry, the halogen atoms are further away than in geometries 3 and 4, reducing the steric repulsion observed by Hermann et al and responsible of the roughening of the surface at full coverage [17]. Structural parameters are summarized in Table 1.…”
Section: Geometrymentioning
confidence: 98%
“…During the last few years this process is also extensively studied experimentally with scanning tunneling microscopes (STM) [1][2][3][4][5][6]. However, the science governing this process and the associated surface rearrangements are not well understood, in spite of the fact that on a Si surface halogen-halogen interactions are extremely short-ranged and dominated mostly by the nearest-neighbor intra-and inter-row repulsions (denoted by a and b, respectively).…”
Section: Introductionmentioning
confidence: 98%